Vulnerability in research ethics: A systematic review of policy guidelines and documents. - Asia Grigis; Giorgia Beretta; Pascal Borry; Virginia Sanchini (PLoS ONE)
Background The history of research involving human subjects has demonstrated the importance of offering everyone an equal opportunity to participate in research, while safeguarding those who require special attention. When it comes to vulnerable individuals, this consideration is relevant. However, disagreement still exists about the meaning of vulnerability, the identification and definition of vulnerable populations, and how these concepts should be operationalised in policy documents in order to implement appropriate, preventive and respectful measures for all those subsumed within this category. Objectives Following the PRISMA-Ethics guidance, we performed a systematic review of policy documents to provide a comprehensive overview of how vulnerability is conceptualised and operationalised in research ethics. The aim is to investigate the meaning and definition of vulnerability in research ethics, its normative justification, the comprehensive set of subjects it refers to, and consequent provisions. Methods Our search centred on three main sources: three overview lists that provide comprehensive coverage of research ethics policy documents and guidelines (the International Compilation of Human Research Standards, the Listing of Social-behavioral Research Standards and the Ethics Legislation, Regulation and Conventions); search databases (PubMed and Web of Science) and grey literature (Google Scholar), to ensure completeness of included policy documents. Search strings were developed by the last author (VS) in consultation with the co-first author (GB). The whole screening process was performed by the first (AG) and co-first author (GB), separately. The search was originally performed in April 2023, and then re-performed in May 2025 to exclude obsolescent results. English-language policy documents in the field of human research ethics and addressing the subject of vulnerability were included. Eligibility criteria covered both national and international application. For data analysis and synthesis, the authors followed the steps of the QUAGOL methodology: policy documents' reading (AG), highlighting of relevant parts (AG), development of a summary of each document's highlighted parts (AG), summary evaluation and verification against previous QUAGOL steps (AG, GB, VS), creation of a comprehensive scheme (AG, GB, VS), and description of results (AG, GB, VS). No automation tools were used at any stage of the review. Results and discussion Seventy-nine policy documents were included in the review. Research findings were organised in four different subsections, corresponding to four research questions. The analysis of such a significant number and variety of documents allowed us to identify several recurring patterns that characterise the way vulnerability is described and addressed by policy documents. Based on our roles as bioethicists, research ethicists, biotechnologies expert in clinical trials, and study coordinators, we identified some key themes, e.g., a tendency to identify and define vulnerable groups, rather than providing a general definition of vulnerability, and a tendency to define vulnerability in relation to informed consent. Conclusions Only a proper understanding of the meaning of vulnerability, its implications and its normative justifications will make it possible to ensure a fair and ethically legitimate participation in research for all involved subjects. As to the study limitation, only publications written in English, or officially translated in English, were included in the review.